Dressed for Ritual, Dressed for Life. A Migration-Period Grave from Sande in Norway. Issue 1 (2nd January 2018) - Vedeler, Marianne; Kristoffersen, Elna Siv; Røstad, Ingunn Marit
Abstract : A RICHLY FURNISHED GRAVE from the migration period in Norway is our starting point for a discussion of the impact of dress in life and death. The Sande farm is situated on the southern tip of Norway on the Lista peninsula, an area renowned for its many rich finds from the migration period. 4 A high-status grave from Sande in Vest-Agder was excavated in 2005 and was found to be lavishly equipped, not least in terms of jewellery items and dress fittings. Some remarkable textile remains were also preserved. The types of adornment and their position in the grave strongly suggest this was the burial of a woman, while the jewellery and textiles and their composition, style and appearance, all offer valuable information on the story of the individual and the dress code of the time. This article offers the first detailed exploration of this burial and its assemblage and an in-depth discussion of the surviving textile fragments and dress equipment as evidence of a form of dress and display that may have operated in life and death .